Dermoscopic Lotus of Learning: Implementation and Dissemination of a Multimodal Dermoscopy Curriculum for Primary Care - Seiverling, Elizabeth (J Med Educ Curric Dev, 2021)
Dermoscopy is a cost-effective tool for detection of skin cancers yet there is limited training available for primary care. The goal of this project was to develop, implement, and disseminate a multimodal curriculum for primary care across a health system based on a previously validated algorithm (Triage Amalgamated Dermoscopic Algorithm; TADA). This cross-sectional study analyzes the dermoscopy workshop intervention of a dermoscopy multimodal curriculum. Volunteers attended one 120-minute dermoscopy workshop on benign and malignant growths using a validated algorithm. Participants took a 30-image pre- and posttest. Survey questions on dermoscopy use, preferences for learning, and skin biopsy performance were included to enhance curriculum development. About 96 participants completed both pre- and postintervention tests. The mean preintervention score (out of 30) was 18.6 and increased to 24.4 on the postintervention evaluation. There was a statistically significant improvement in scores for both benign and malignant skin growths after the intervention (P < .05). Short dermoscopy workshops have a positive intervention effect when training primary care providers to identify images of benign and malignant dermoscopic skin lesions. A multimodal dermoscopy curriculum allows learners to build on initial training using spaced review and blended learning strategies. The “Dermoscopic Lotus of Learning” has the potential to be a model for other primary care residency programs. A healthy partnership between dermatologists and primary care is essential.